OPTIMASI PRODUKSI OLAHAN RUMPUT LAUT DI UMKM XYZ MENGGUNAKAN METODE BRANCH AND BOUND - Indah Nur Aini; Mikhratunnisa Mikhratunnisa (Matematika Sains, 2023)
MSME XYZ is one of the active UMKM and has considerable market potential in West Sumbawa Regency. The problem commonly faced by UMKM, especially MSME XYZ is how to properly combine production factors or resources owned to obtain maximum profit. This study aimed to determine the production process's optimization and the maximum profit obtained by MSME XYZ by using the branch and bound method. Based on the study's results, it was obtained that for effective optimization of the production process, MSME XYZ should produce 16 packages of seaweed sticks, 11 packages of seaweed dodol, 8 packages of seaweed brownies, and 4 packages of seaweed ice cream in one production. So that the total profit from each type of product in each package is Rp. 243.700 for one-time production. The maximum profit obtained by MSME XYZ in one production is Rp. 110.712 and an increase in profits of 5,7% from factual conditions